2005
DOI: 10.1097/01.mao.0000185065.04834.95
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Anchored Hearing Aids in Unilateral Inner Ear Deafness: An Evaluation of Audiometric and Patient Outcome Measurements

Abstract: The poor sound-localization results in an audiologic test setting illustrated the inability of patients with unilateral inner ear deafness to localize sounds. The speech-in-noise measurements demonstrated the efficacy of the BAHA CROS to lift the head shadow. Patients were still satisfied at 1-year follow-up, according to the four instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
160
3
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(184 citation statements)
references
References 25 publications
(31 reference statements)
15
160
3
6
Order By: Relevance
“…Vaneecloo et al considered that the restoration of stereo audiometric effect resulting from Baha was a good criterion for implantation -specifically an improvement in understanding of speech-in-noise of over 10% [Vaneecloo et al, 2000]. Using this selection method, Vaneecloo et al reported a high satisfaction rate, which was later confirmed by other groups [Niparko et al, 2003;Hol et al, 2005]. The majority of these studies either focused on satisfaction following Baha-mediated rehabilitation or on comparing satisfaction resulting from various means of rehabilitation for unilateral deafness [Hol et al, 2010].…”
Section: Introductionsupporting
confidence: 62%
“…Vaneecloo et al considered that the restoration of stereo audiometric effect resulting from Baha was a good criterion for implantation -specifically an improvement in understanding of speech-in-noise of over 10% [Vaneecloo et al, 2000]. Using this selection method, Vaneecloo et al reported a high satisfaction rate, which was later confirmed by other groups [Niparko et al, 2003;Hol et al, 2005]. The majority of these studies either focused on satisfaction following Baha-mediated rehabilitation or on comparing satisfaction resulting from various means of rehabilitation for unilateral deafness [Hol et al, 2010].…”
Section: Introductionsupporting
confidence: 62%
“…However, performance was still significantly poorer than that reported in studies of bilaterally implanted subjects [Grantham et al, 2008]. Other studies could not confirm improvement in localization in unilaterally implanted subjects [Hol et al, 2005;Verschuur et al, 2005].…”
contrasting
confidence: 40%
“…CROS is an adjunct which has been used for several years in patients with single-sided deafness. There is evidence from the literature that patients with singlesided deafness have a significantly better signal-to-noise ratio (SNR) when fitted with a CROS device than unaided patients [Hol et al, 2005;Lotterman and Kasten, 1971]. However, a CROS device has never been studied as an aid to patients with a unilateral CI, a condition which has some similarities to single-sided deafness.…”
mentioning
confidence: 99%
“…10 In addition, the patient with partial or no hearing recovery, or persistent tinnitus, will require ongoing management from otolaryngological, audiological, and psychological perspectives. 11 This guideline is intended for all clinicians who diagnose or manage adult patients (age 18 years and older) who present with SHL. After addressing causes, diagnosis, and treatments of non-SSNHL briefly, this guideline will address SSNHL in detail.…”
mentioning
confidence: 99%